Technological Populism and its Archetypes: Blockchain and Cryptocurrencies - Cătălin-Gabriel Stănescu; Asress Adimi Gikay (Nordic Journal of Commercial Law, 2019)
Blockchain technology claims to disrupt the existing financial system, the way of doing business, and to empower ordinary citizens against an elitist economy through decentralization of the decision-making process. In the political arena, the disruptive ideology branded as ‘populism’ challenges the neo-liberal establishment. By appealing to peoples’ fears, frustrations, and dissatisfaction with the political elites, exploiting distrust in the so-called establishment, populism claims to deliver more power to the people.